1999
DOI: 10.1016/s0741-5214(99)70278-8
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of endoscopic perforator vein interruption for chronic venous insufficiency: Lessons learned from the North American Subfascial Endoscopic Perforator Surgery registry

Abstract: Severe chronic venous insufficiency (CVI) can be highly debilitating, and successful treatment is fraught with difficulty, patient noncompliance, and recurrence, despite the initial success of the treatment. Because there is no pharmacologic intervention that is beneficial, surgical treatments have been explored. The perforating veins became targets for surgical therapy in the late 1930s, 1 but it was the development of endoscopic subfascial surgery in German-speaking countries during the 1980s 2,3 that attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
1
15

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(237 citation statements)
references
References 35 publications
11
209
1
15
Order By: Relevance
“…A multicenter study involving 148 SEPS procedures in patients with active and healed venous ulcers demonstrated accumulative ulcer healing of 88% at 1 year and an ulcer recurrence of 28% at 2 years. 83 SEPS also can be used in conjunction with superficial vein ablation with 91% ulcer healing at a mean of 2.9 months, and is accompanied by a significant improvement in the clinical severity and venous disability scores. 84 In a large study evaluating 832 patients with CEAP clinical classes 4 to 6 for 9 years, 55% of patients underwent both SEPS and ligation and stripping of the superficial venous segments.…”
Section: Subfascial Endoscopic Perforator Surgerymentioning
confidence: 99%
“…A multicenter study involving 148 SEPS procedures in patients with active and healed venous ulcers demonstrated accumulative ulcer healing of 88% at 1 year and an ulcer recurrence of 28% at 2 years. 83 SEPS also can be used in conjunction with superficial vein ablation with 91% ulcer healing at a mean of 2.9 months, and is accompanied by a significant improvement in the clinical severity and venous disability scores. 84 In a large study evaluating 832 patients with CEAP clinical classes 4 to 6 for 9 years, 55% of patients underwent both SEPS and ligation and stripping of the superficial venous segments.…”
Section: Subfascial Endoscopic Perforator Surgerymentioning
confidence: 99%
“…Since its first description by Hauer in the 1980s, 1) SEPS has been accepted as an improved treatment modality in the surgical treatment of perforating vein insufficiency, particularly in cases with advanced skin changes. SEPS is performed in some facilities in North America [2][3][4][5] and Europe [6][7][8][9][10] as a component of the comprehensive treatment program for venous insufficiency. These previous studies presented favorable results with SEPS.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure is associated with much less scarring and a faster recovery than the open method. The North American registry confirmed a low 2-year recurrence rate of venous ulcers and a more rapid ulcer healing with the laparoscopic method of perforator interruption [10]. In a recent study using subfascial balloon dissection and interruption of incompetent perforating veins (usually in conjunction with great saphenous vein ligation and stripping), 92 % of patients exhibited significant improvement of venous stasis ulcers within 4-14 weeks [11].…”
Section: Discussionmentioning
confidence: 91%